In- and Out-Group Effects on Social Perception and Empathy in Cocaine Use Disorder - Aue, Tatjana; Kexel, Ann-Kathrin; Kluwe-Schiavon, Bruno; Bührer, Stephanie; Baumgartner, Markus R.; Soravia, Leila M.; Quednow, Boris B. (Frontiers in Psychiatry, 2022)
Earlier research revealed that cocaine users display impairments in emotional but not necessarily in cognitive empathy. However, no study to date has tested whether empathy is generally altered or whether impairments are restricted to specific social targets. The current investigation addresses this open question. In addition, we examined whether attributions of warmth and competence as well as personal future expectancies differed between cocaine users and substance-naïve controls. Twenty-two chronic cocaine users and 40 stimulant-naïve controls specified their perceived warmth and competence for four social targets [in-group member, opposite consumption out-group member (cocaine user for controls and non-user for cocaine user), opposite consumption out-group member of opposite gender, and elderly person]. They also specified their cognitive and emotional empathy for these four targets facing eight desirable and eight undesirable events. Finally, they rated the likelihood of these scenarios happening to themselves. Both cocaine users and controls attributed lower warmth to cocaine-using than non-using targets. Comparably, no in-group preference was observed in cocaine user’s emotional empathy ratings, and greater denigration of the in-group was associated with higher frequency and doses of cocaine consumption. In addition, cocaine users rated both desirable and undesirable events as more likely to happen to themselves than did controls. Results show that substance-naïve individuals stigmatize cocaine users. They further point to compromised self-esteem in cocaine users resulting from such stigmatization. Interventions should address stigmatization processes to break the vicious circle of mutual social distancing and stronger dedication to the drug.